PENGEMBANGAN MODUL BERBASIS PENEMUAN (DISCOVERY LEARNING) MATERI PLANTAE UNTUK SISWA KELAS X SMA/MA - Sarwati, Sarwati; Marhamah, Marhamah; Yuliana, Lia (UNIVERSITAS HAMZANWADI, 2022)
This study aims to develop a Discovery Learning Module for Plantae Materials for Class X SMA/MA students. This type of research is development research. The model used in this research and development is the Bord and Gall model using only 5 stages, namely (Research and information gathering, planning, early product development, early stage field trials, and early product revisions). Thevalidators consist of 1 material expert, 1 media/design expert, and 2 biology teachers. The respondents consisted of 10 students of class XI IPA MA Darul Mahmudien NW Montong Gamang for the 2021/2022 academic year. The data collection technique used a questionnaire with a Likert scale of 5 to a scale of 4 according to the researcher's modification. Data were analyzed using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, it can be concluded that the product of teaching materials in the form of modules developed has good criteria, both in terms of material (71.3%), in terms of teachingmaterial design (72.85%), Biology teachers (80.31%) and student responses (81.12 %). Thus, this module is suitable for use in the learning process.